Montaje, tramas paralelas e ironía dramática en el relato cinematográfico - Sarmiento Herencia, Diego Alonso (2020)
Cinema is young narrative phenomenon. Given that its development has been —and continues to be— vertiginous, it is, sometimes, quite difficult to explain. The different elements that play a part in the development of stories —images, sounds, montage, etc.— are so many and so different that to explain or define them is too grand a chore for a single document. This paper aims at identifying and describing, from the relations between cinema and literature, and from an structural point of view, the montage technics, the construction of parallel storylines and dramatic irony, all of which are important components of modern cinema.